2016
DOI: 10.1016/j.bbacli.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Blood metabolomics analysis identifies abnormalities in the citric acid cycle, urea cycle, and amino acid metabolism in bipolar disorder

Abstract: BackgroundBipolar disorder (BD) is a severe and debilitating psychiatric disorder. However, the precise biological basis remains unknown, hampering the search for novel biomarkers. We performed a metabolomics analysis to discover novel peripheral biomarkers for BD.MethodsWe quantified serum levels of 116 metabolites in mood-stabilized male BD patients (n = 54) and age-matched male healthy controls (n = 39).ResultsAfter multivariate logistic regression, serum levels of pyruvate, N-acetylglutamic acid, α-ketoglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 67 publications
4
63
0
Order By: Relevance
“…In a metabolomics study that also used only male patients and HC, Yoshimi et al . reported elevated mean serum lactate, though not significant ( P = 0.321), for BD patients ( n = 54) in comparison to HC ( n = 40) . This study used the same subject population as another Yoshimi et al .…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…In a metabolomics study that also used only male patients and HC, Yoshimi et al . reported elevated mean serum lactate, though not significant ( P = 0.321), for BD patients ( n = 54) in comparison to HC ( n = 40) . This study used the same subject population as another Yoshimi et al .…”
Section: Resultsmentioning
confidence: 84%
“…reported a significant lactate increase in the red blood cells of lithium‐treated BD patients and this increase is likely confounded by the fact that the blood sat at room temperature . Interestingly, the other two studies that did not report any significant differences in the peripheral lactate levels in BD compared to HC, excluded female participants. For these reasons, it is difficult to draw conclusions from the peripheral lactate data in BD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bipolar disorder (BD), formerly called manic depression, causes extreme mood swings that include emotional highs (mania or hypomania) and lows (depression). Three groups published using 3 different sample types, plasma [137], CSF [130] and serum [136] to both understand the biology of BD and seek biomarkers for diagnosis. Hashimoto [130] aptly used the specificity of CE-MS to understand the role of mitochondrial dysfunction in BD, finding isocitrate as a diagnostic biomarker in CSF.…”
Section: Medical Applicationsmentioning
confidence: 99%
“…Yoshimi and colleagues obtained additional evidences corroborating the theory of mitochondrial dysfunction in BD. Through metabolomic assays of cerebrospinal fluid (CSF) obtained from BD patients, they observed that deregulation of isocitrate metabolism in the mitochondrial citric acid cycle is relevant in the pathogenesis of BD [87]. Moreover, mitochondrial dysfunction has been identified as the cause of the neuroprogression and cognitive impairment observed in BD.…”
mentioning
confidence: 99%